Numerical simulation of layer thickness optimization in perovskite solar cells for enhanced power conversion efficiency - Soni Prayogi (Universitas Gadjah Mada, 2025)
Perovskite solar cells (PSCs) have gained significant attention due to their remarkable power conversion efficiency (PCE) and potential for low-cost, scalable production. Despite this progress, further efficiency enhancement requires systematic optimization of device architecture, particularly the thickness of functional layers. This study presents a numerical simulation using the OGMANANO simulation platform to investigate the influence of layer thickness variation, specifically in the perovskite absorber layer, electron transport layer (ETL), and hole transport layer (HTL), on the performance of planar PSCs. The simulation models a typical n-i-p structured device under standard AM1.5G illumination, evaluating key photovoltaic parameters such as short-circuit current density (Jsc), open-circuit voltage (Voc), fill factor (FF), and overall PCE. Results indicate that the optimal absorber thickness lies in the 500–600 nm range, with a peak efficiency of 22.7% achieved at 550 nm. Furthermore, ETL and HTL show optimal performance at 50 and 60 nm, respectively, minimizing recombination losses and enhancing charge transport. The study concludes that precise layer thickness control is critical for maximizing PSC efficiency. The use of OGMANANO proved effective in simulating multilayer perovskite structures, providing a reliable tool for pre-fabrication optimization in advanced solar cell design.